An in vitro study of the effects of respiratory circuit setup and parameters on aerosol delivery during mechanical ventilation - Reilly, Leanne; Mac Giolla Eain, Marc; Murphy, Sarah; O’Sullivan, Andrew; Joyce, Mary; MacLoughlin, Ronan (Frontiers in Medicine, 2024)
Aerosol therapy is often prescribed concurrently during invasive mechanical ventilation (IMV). This study determines the effects of nebuliser position, circuit humidification source, and most importantly, lung health on the delivery of aerosol in simulated adult and paediatric IMV patients. Furthermore, the influence of closed suction catheters on aerosol delivery is also addressed.A vibrating mesh nebuliser was used to delivered Albuterol to simulated adult and paediatric IMV patients with differing states of lung health. Four different nebuliser positions and two types of humidification were analysed. Closed suction catheter mounts, a mainstay in IMV therapy, were incorporated into the circuits. The mean ± SD dose of aerosol (%) was assayed from a filter at the distal end of the endotracheal tube.Nebuliser placement and circuit humidification source had no effect on the delivered dose (%) in adults, yet both significantly did in the simulated paediatric patients. The use of closed suction catheter mounts significantly reduced the delivered dose (%) in adults but not in paediatric patients. A simulated healthy lung state generated the largest delivered dose (%), irrespective of nebuliser position in the adult. However, different lung health and nebuliser positions yielded higher delivered doses (%) in paediatrics.Lung health and respiratory circuit composition significantly affect aerosol delivery in both adult and paediatric IMV patients. Nebuliser placement and respiratory circuit humidification source do not affect the delivered dose in adult but do in paediatric IMV patients.